Topiramate causing type II renal tubular acidosis: A case and review of the mechanism - Chahin, Michael (Clin Case Rep, 2020)
Topiramate has a wide array of pharmacologic effects, including proximal renal tubular acidosis (RTA). Clinicians must be wary of the possibility for development of somnolence due to compensatory hyperventilation and cardiac dysrhythmias.